1998
DOI: 10.1046/j.1365-2141.1998.00623.x
|View full text |Cite
|
Sign up to set email alerts
|

The myeloma cell antigen syndecan‐1 is lost by apoptotic myeloma cells

Abstract: Summary. Syndecan-1 is a cell membrane proteoglycan that binds extracellular matrix components and various growth factors. It is expressed only on malignant plasma cells in bone marrow samples from patients with multiple myeloma (MM). Several reports have suggested that syndecan-1 was present only on a part of the myeloma cells. By using either IL-6-dependent myeloma cell lines or primary myeloma cells stained by annexin V, we report here that syndecan-1 was rapidly lost by myeloma cells undergoing apoptosis. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
79
2
3

Year Published

1999
1999
2021
2021

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 126 publications
(91 citation statements)
references
References 25 publications
7
79
2
3
Order By: Relevance
“…After 6 days, cell viability was measured by CD138-FITC (IQ products, Groningen, The Netherlands; clone B-A38)/PI (Pharmingen) staining and referred to the medium control (Jourdan et al, 1998). PI of 1 ml at the concentration of 50 mg/ ml was used.…”
Section: Survival Of Primary Mmcsmentioning
confidence: 99%
“…After 6 days, cell viability was measured by CD138-FITC (IQ products, Groningen, The Netherlands; clone B-A38)/PI (Pharmingen) staining and referred to the medium control (Jourdan et al, 1998). PI of 1 ml at the concentration of 50 mg/ ml was used.…”
Section: Survival Of Primary Mmcsmentioning
confidence: 99%
“…We have shown that the MI15 mAb recognizes syndecan-1 and that syndecan-1 is only present in tumoral samples on viable myeloma cells. 27,28 In addition, this antigen is cleaved by chymopapain without affecting cell viability using a procedure previously described for CD34 purification which allows a large scale purification of myeloma cells. 29 To purify myeloma cells, mononuclear cells from tumoral samples were suspended in Hank's buffer containing 1% of human serum albumin (Hank's/HSA) and 0.5% human Ig at a concentration of 2 × 10 7 cells/ml and incubated for 30 min at 4°C.…”
Section: Purification Of Freshly Explanted Primary Myeloma Cellsmentioning
confidence: 99%
“…CD138, also known as syndecan-1, is a sulphate-rich proteoglycan adhesion molecule usually expressed during B-cells differentiation into plasma cells (Jourdan et al, 1998). Two studies proposed the positive expression of CD138 as a marker of poor prognosis in DLBCL patients (Hoffmann et al, 2005;Oh and Park, 2006).…”
Section: Introductionmentioning
confidence: 99%